Interaction Between Sulfur and Iron in Plants - Astolfi, Stefania; Celletti, Silvia; Vigani, Gianpiero; Mimmo, Tanja; Cesco, Stefano (Frontiers in Plant Science, 2021)
It is well known that S interacts with some macronutrients, such as N, P and K, as well as with some micronutrients, such as Fe, Mo, Cu, Zn and B. From our current understanding, such interactions could be related to the fact that i) S shares similar chemical properties with other elements (e.g. Mo, Se) determining competition for acquisition/transport process (SULTR transporter family proteins); ii) S-requiring metabolic processes need the presence of other nutrients or regulate plant responses to other nutritional deficiencies (S-containing metabolites are precursor for the synthesis of ethylene and phytosiderophores); iii) S directly interacts with other elements (e.g. Fe) by forming complexes and chemical bonds, such as Fe-S clusters; iv) S is a constituent of organic molecules, which play crucial roles in plants (glutathione, transporters, etc). This review summarizes the current state of knowledge of the interplay between Fe and S in plants. In this context, it has been demonstrated that plant capability to take up and accumulate Fe is strongly dependent on S availability in the growth medium in both grasses and dicot plants. Moreover, it has been demonstrated that providing S above the average nutritional need allows to enhance the Fe content in wheat grain, being this beneficial effect particularly pronounced under severe Fe limitation. On the other hand, it has been demonstrated that Fe deficiency condition induces a significant increase in the demand for S resulting in increased S uptake and assimilation rate, similarly to what happens under S deficiency condition. The critical evaluation of the recent studies on the modulation of Fe/S interaction by integrating old and new insights gained on this topic will help to identify the main gaps in our knowledge. Indeed, it remains a challenge to determine how the interplay between S and Fe is regulated and how plants are able to sense environmental nutrient fluctuations and then, to adapt their uptake, translocation, assimilation, and signaling. A better knowledge of the mechanisms of Fe/S interaction might considerably help in improving crop performance within a context of limited nutrient resources and a more sustainable agriculture.